Effect of Relining Curing Methods on Some Properties of Acrylic Resin Denture Base (Part II) - Nadira A Hatim; Aliaa W AL-Omari (University of Mosul, College of Dentistry, 2013)
Aims: To investigate the effect of relining by using two curing methods (water bath, or microwave) on some properties ( surface hardness, color property, residual monomer, and porosity) of relined acrylic resin denture base. Materials and methods: The study was done by preparing 320 samples, divided into two parts, the first part involved studying surface hardness, color property, residual monomer, and porosity of samples representing a denture base cured by water bath curing method, and the samples of second part cured by microwave curing method, then the effect of relining by the two curing methods (water bath, and microwave) were evaluated. Samples with dimensions of 30×15×3 ± 0.03mm for the indentation hardness test, 45×10×2.5mm for the color property test, 20×20×3mm for residual monomer test were prepared in this study. Analysis of variance (ANOVA) and Duncan's multiple range tests were used for statistical analysis. Results: surface hardness of denture base cured by microwave was significantly higher (at P=0.05) than denture base cured by water bath, all the relined samples has sig-nificant higher absorbance, and showed that the elusion of monomer was higher at the 1st day. Conclu-sions: Surface hardness, color property and residual monomer of the acrylic resin denture base were affected by relining. Microwave curing method gave better mechanical, and physical properties of the relined acrylic resin denture base, the amount of residual monomer was less in the microwave curing method. Both curing methods gave samples free from porosities.